2014
DOI: 10.1159/000355811
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Renal Effects of Atrasentan in Combination with Enalapril and Paricalcitol in Uremic Rats

Abstract: Background/Aims: The search for new therapies providing cardiorenal protection in chronic kidney disease (CKD) has led to treatments that combine conventional renin-angiotensin-aldosterone-system inhibitors with other drugs that exhibit potential in disease management. Methods: In rats made uremic by renal ablation, we examined the effects of addition of the endothelin-A receptor antagonist atrasentan to a previously examined combination of enalapril (angiotensin converting enzyme inhibitor) and paricalcitol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…When the duration of treatment was only 20 weeks, the positive effects were not observed (Vaněčková et al 2012). This is consistent with a study in 5/6 nephrectomized female Sprague Dawley rats in which a three-month treatment with atrasentan in combination with enalapril (ACEi) and paricalcitol (vitamin D activator) had no additional renoprotective effects as compared to the treatment with enalapril alone (Ritter et al 2014). Unfortunately, beneficial effects were also not demonstrated in TGR rats in which the long-term treatment with ET A blockade on top of RAS blockade was delayed to the phase of established hypertension and CKD (Sedláková et al 2017).…”
Section: Endothelin Antagonists In Experimental Non-diabetic Ckdsupporting
confidence: 87%
“…When the duration of treatment was only 20 weeks, the positive effects were not observed (Vaněčková et al 2012). This is consistent with a study in 5/6 nephrectomized female Sprague Dawley rats in which a three-month treatment with atrasentan in combination with enalapril (ACEi) and paricalcitol (vitamin D activator) had no additional renoprotective effects as compared to the treatment with enalapril alone (Ritter et al 2014). Unfortunately, beneficial effects were also not demonstrated in TGR rats in which the long-term treatment with ET A blockade on top of RAS blockade was delayed to the phase of established hypertension and CKD (Sedláková et al 2017).…”
Section: Endothelin Antagonists In Experimental Non-diabetic Ckdsupporting
confidence: 87%
“…These findings are consistent with findings in uremic and/or hypertensive rat models. In these rats it was shown that an ETA receptor blocker reduces the size of myocytes in a blood pressure independent manner [42,43].…”
Section: Kidney Weight and Protein Excretionmentioning
confidence: 99%
“…Although some treatment studies in animal models of CKD show a reduction of cardiac hypertrophy without lowering blood pressure (41, 59, 176, 198, 209211), thereby uncoupling cardiac injury from hypertension in the context of kidney injury, it is most likely that in CKD increases in blood pressure together with a variety of other factors, such as serum elevations of FGF23 and uremic toxins (212), synergistically contribute to cardiac injury. In fact, FGF23 might directly contribute to hypertension by targeting the renal renin-angiotensin system (205) and by regulating renal sodium handling via targeting the distal tubules (213).…”
Section: The Role Of Fgf23 In Uremic Cardiomyopathymentioning
confidence: 99%